2015
DOI: 10.1161/jaha.115.001779
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cancer and Cardiovascular Outcomes Following Percutaneous Coronary Intervention

Abstract: BackgroundCardiovascular disease and cancer increasingly coexist, yet relationships between cancer and long-term cardiovascular outcomes post–percutaneous coronary intervention (PCI) are not well studied.Methods and ResultsWe examined stented PCI patients at Duke (1996–2010) using linked data from the Duke Information Systems for Cardiovascular Care and the Duke Tumor Registry (a cancer treatment registry). Our primary outcome was cardiovascular mortality. Secondary outcomes included composite cardiovascular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 27 publications
2
33
0
2
Order By: Relevance
“…26 Another study indicated that patients who were diagnosed with cancer up to 1 year before receipt of PCI did not experience worse long-term cardiovascular outcomes compared with those who did not have cancer. 27 We observed that cancer survivors aged 65 years received similar rates of post-AMI cardiovascular pharmacotherapies, except for marginally less rates of ACEi/ARB, oral anticoagulants, and statins. The precise reason for less prescription of these medications is difficult to discern from our data set given the lack of granular data.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…26 Another study indicated that patients who were diagnosed with cancer up to 1 year before receipt of PCI did not experience worse long-term cardiovascular outcomes compared with those who did not have cancer. 27 We observed that cancer survivors aged 65 years received similar rates of post-AMI cardiovascular pharmacotherapies, except for marginally less rates of ACEi/ARB, oral anticoagulants, and statins. The precise reason for less prescription of these medications is difficult to discern from our data set given the lack of granular data.…”
Section: Discussionmentioning
confidence: 61%
“…Analysis of a multicenter registry suggested that patients who had a cancer diagnosis up to, but not longer than, 6 months before an AMI and received PCI had significantly worse 1‐year mortality compared with patients without cancer who had an AMI . Another study indicated that patients who were diagnosed with cancer up to 1 year before receipt of PCI did not experience worse long‐term cardiovascular outcomes compared with those who did not have cancer …”
Section: Discussionmentioning
confidence: 99%
“…28 However, available data offer conflicting views on the safety of these procedures among lower-risk cancer patients. 29,30 Additionally, patients with cancer had higher 30 day readmission rates than had non-cancer patients; however, HF-related readmission rates were higher in the non-cancer cohort, when compared with cancer patients. This discrepancy is likely related to cancer-specific morbidities such as infection, anaemia, or thrombosis.…”
Section: Heart Failure Admissions In Cancermentioning
confidence: 96%
“…Eş zamanlı kanser ve kalp damar hastalığı tedavisi ile ilgili yayınlar son yıllarda artmakla birlikte yeterli sayı ve çeşitliliğe ulaşmamıştır (4,5). Yayınlardaki hasta sayıları az, takip süreleri kısadır.…”
Section: Görülme Sikliği (Incidense)unclassified